Young children do not require perceptual-motor feedback to solve Aesop’s Fable tasks - Rachael Miller; Sarah A. Jelbert; Elsa Loissel; Alex H. Taylor; Nicola S. Clayton (PeerJ, 2017)
Aesop’s Fable tasks—in which subjects drop objects into a water-filled tube to raise the water level and obtain out-of-reach floating rewards —have been used to test for causal understanding of water displacement in both young children and non-human animals. However, a number of alternative explanations for success on these tasks have yet to be ruled out. One hypothesis is that subjects may respond to perceptual-motor feedback: repeating those actions that bring the reward incrementally closer. Here, we devised a novel, forced-choice version of the Aesop’s Fable task to assess whether subjects can solve water displacement tasks when this type of feedback is removed. Subjects had to select only one set of objects, or one type of tube, into which all objects were dropped at once, and the effect the objects had on the water level was visually concealed. In the current experiment, fifty-five 5–9 year old children were tested in six different conditions in which we either varied object properties (floating vs. sinking, hollow vs. solid, large vs. small and too large vs. small objects), the water level (high vs. low) and/or the tube size (narrow vs. wide). We found that children aged 8–9 years old were able to solve most of the water displacement tasks on their first trial, without any opportunity for feedback, suggesting that they mentally simulated the results of their actions before making a choice. Children aged 5–7 years solved two conditions on their first trial (large vs. small objects and high- vs. low-water levels), and learnt to solve most of the remaining conditions over five trials. The developmental pattern shown here is comparable to previous studies using the standard Aesop’s Fable task, where eight year olds are typically successful from their first trial and 5–7 year olds learn to pass over five trials. Thus, our results indicate that children do not depend on perceptual-motor feedback to solve these water displacement tasks. The forced-choice paradigm we describe could be used comparatively to test whether or not non-human animals require visual feedback to solve water displacement tasks.